Problems in the Implementation of Law Number 16 of 2019 Concerning the Marriage Age Limit in Rupit District, North Musi Rawas Regency - Ardi Akbar; Rifanto Bin Ridwan (al-Afkar, Journal For Islamic Studies, 2026)
In terms of its impact, early marriage in North Musi Rawas Regency often leads to various social problems such as school dropouts, poverty, and early divorce. Girls who marry underage tend to have limited access to education and healthcare and are more vulnerable to domestic violence. North Musi Rawas Regency, particularly Rupit Sub-District, still faces significant challenges in reducing the rate of early marriage. According to data from the local Office of Women's Empowerment and Child Protection (DP3A), the rate of underage marriage in this area remains relatively high compared to the national average. The main contributing factors include economic pressure, low levels of education, and strong cultural and customary influences that perceive marriage as a solution to prevent promiscuity and uphold family honor. This research employs a qualitative approach with a case study method. The main focus of this study is the effectiveness of implementing the legal minimum age of marriage in preventing early marriage in Rupit Sub-District, North Musi Rawas Regency. The case study method was chosen to comprehensively explore how the age restriction policy is applied and to what extent it is effective in reducing early marriage. This method also allows the collection of data from various sources, such as in-depth interviews, observations, and document analysis, to gain a thorough understanding of the phenomenon being studied. The findings indicate that the implementation of the legal minimum age of marriage in Rupit Sub-District still faces complex structural and cultural barriers. Law Number 16 of 2019 is normatively progressive; however, its effectiveness depends heavily on public education, economic empowerment, reform of religious courts, and the active roles of local leaders and religious figures. When the law fails to align with or is even rejected by social realities, its effectiveness becomes merely formalistic. In Rupit Sub-District, Law No. 16 of 2019 functions more as an administrative requirement for filing marriage dispensations than as a substantive tool to prevent early marriage. The implementation of the legal minimum age of marriage as mandated in Law Number 16 of 2019 aims primarily to reduce child marriage rates, strengthen the protection of children's and women's rights, and foster families that are physically, mentally, and socially prepared.